THE INFLUENCE OF SELF-COMPASSION AND EMOTION REGULATION ON THE PSYCHOLOGICAL WELL-BEING OF WORKING PARENTS WHO HAVE CHILDREN WITH SPECIAL NEEDS - Putri, Kania Rachmadira; Lely Ika Mariyati (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to determine the influence of self-compassion and emotion regulation on the psychological well-being of working parents with special needs children. Method: This study uses a correlational quantitative approach, involving 68 working parents as the sample. The sample was determined using the accidental sampling technique at 4 special schools in the Sidoarjo District area. The instruments in this study consist of 3 psychological scales, namely: Psychological Well-Being Scales (PWB), Neff's Self-Compassion Scale, and Cognitive Emotion Regulation Questionnaire (CERQ). The analysis technique used multiple regression analysis with the help of JASP 0.18.1 software. Results: The analysis results (F (2.65) = 12.133; P < .001) indicate that self-compassion and emotion regulation simultaneously have an impact on psychological well-being. Novelty: The implication of this research is as a basis for counseling-based intervention programs to enhance the self-compassion and emotional regulation abilities of working parents with children with special needs to achieve psychological well-being.